GAMBARAN ASUPAN FAST FOOD, AKTIVITAS FISIK, DAN SCREEN TIME DENGAN STATUS GIZI PADA SISWA DI SMP HANG TUAH 2 JAKARTA SELATAN - Titus Priyo Harjatmo; Nafida Febriyanti; Trina AStuti; Moch Rachmat (Jurnal GIZIDO, 2022)
Nutritional status is a meansure of success in fulfilling nutrition for children as indicated by weight and height, the nutritional problems that most often occur inadolescents are lack of nutritional intake and excess nutritional intake that can lead to obesity. The purpose of this study was to determine the description of fast food intake, phsycal activity and screen time on nutritional status of students at Hang Tuah 2 Junior High School, South Jakarta. This research was conducted at Hang Tuah 2 Junior High School, South Jakarta for 2 weeks in a row. This research is descriptive with a cross sectional approach. Sampling was done by using a simple random sampling method and the number of samples was 70 people. The results of this study showed that stundents with obese nutritional status (22.8%) and overweigth nutritional (57.2%) were found to be more than students with normal nutritional status (20%). Based on the intake of fast food, students have more frequent consumption of fast food, which is 74.3% of students. Based on phsycal activity, most of the students did physical activity which was classified into the light activity category (85.7%). Based on the duration of screen time, students who have overweight and obese nutritional status are more likely to have screen time duration always compared to students who have normal nutritional status.